Can quantative analysis boost qualitiy? An empirical research for Turkish administered justice, health and education systems - Kapancı, Kadir Berk (..., 2022)
Justice, health and education systems are the most important pillars of the social state. As a social state, Turkey undertakes in its Constitution to provide state administered justice(art.9), health (art. 56) and education (art. 42). Undoubtedly, the accessibility, quality and reliability of these systems would also increase the trust in the state. However, the efficiency of these relevant services is highly debated in Turkey. The aim of this research is to examine whether performance-based evaluations are included in these relevant systems and also discuss possible suggestions for all three systems. The research consists of three sections:The first section aims to evaluate the performance-based quantitative assessment in the state administered justice system in Turkey. In this system, the performance-based quantitative assessment is used mainly for the purposes of promotion of the judges and the prosecutors. The second section aims to evaluate a possible system of performance-based quantitative assessment in the public health system in Turkey. The third section aims to evaluate a possible system of performance-based quantitative assessment in the education system in Turkey. Accordingly, this research aims to analyze whether it is possible to develop high tech performance-based quantitative assessment systems to boost quality in the justice, health and education services, further to evaluate the extent of the human supervision in order to ensure the compliance to legal rights of individuals in order to prevent possible unexpected and unwanted violations(especially in the field of personal data protection) without enabling any undue influence based on subjective values.
Keywords: Performance; Quantitative analysis; Education system; Public health system; Justice system